Mood instability and functional recovery in bipolar disorders. (20th January 2013) - Strejilevich, S. A.; Martino, D. J.; Murru, A.; Teitelbaum, J.; Fassi, G.; Marengo, E.; Igoa, A.; Colom, F.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to identify psychopathological factors associated with long‐term functional outcome in euthymic bipolar disorder patients and to test new measures of mood instability and symptoms intensity. Method Fifty‐five patients with more than 12 months of follow‐up were included. In addition to traditional clinical variables, the time spent ill was documented using a modified life‐charting technique based on NIHM life‐charting method. New measures, Mood Instability Factor, and Mood Intensity Factor were defined and assessed. Functioning Assessment Short Test (FAST) was used to assess disability. Results The follow‐up period was 3.00 ± 1.51 years. Weeks with subsyndromal depressive symptoms (β = 0.133, t = 2.556, P = 0.014), weeks with mild manic symptoms (β = 1.441, t = 3.10, P = 0.003), and the Mood Instability Factor (β = 0.105, t = 3.593, P = 0.001) contributed to approximately 46% of the FAST total score variance. Conclusion New methodologies including subsyndromal symptoms and mood instability parameters might contribute to understand the worse long‐term functional outcome that affects a considerable percentage of BD patients even after episode remission. Concerns about therapeutic approaches are discussed.